Network interrupts : - Brown, Ralf (Addison-Wesley, 1994)
Network Interrupts draws together in one volume all the information about network system calls, including NetWare 4.0, NetWare Lite, Windows for Workgroups, and Windows NT. This book is an essential resource for all application programmers writing software that has to be network-aware.